Salivary Cortisol Levels Representing Serum Cortisol Levels in Atopic Dermatitis Patients - Novia Indriyani Adisty; Marsudi Hutomo; Diah Mira Indramaya (Faculty of Medicine, Universitas Airlangga, 2015)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin disorder, recurrent lesion with a distinctive and specific distribution of lesions according phases. Patients with allergic diseases have been known to have a variety of patterns of cortisol. Dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis and the role of cortisol has been studied in patients with DA. Free cortisol adrenal cortex is considered biologically active, which passively diffuses into all body fluids including saliva. Another advantage is the saliva examination is non-invasive, stress free and easy to do anywhere. Purpose: To analyze the correlation between levels of serum cortisol and salivary cortisol in patients with AD. Methods: Analytical, observational, cross-sectional study of the 29 AD patients who underwent blood and saliva samples by the method of